(untitled) (Physical Culture and Sport: Scientific Perspective, 2024)
According to statistics, the number of children with a low level of physical fitness is constantly growing. Most scientists attribute this to a sedentary lifestyle, which is the reason why children spend most of their time in a static sitting position during study, homework preparation, almost do not attend sports sections, but prefer games on the computer or phone, and spend little time outdoors. Therefore, the main task is to increase the level of motor activity, which, in turn, will contribute to an increase in the level of physical fitness. Among such means, swimming is worth highlighting, which ensures the redistribution of muscle tension, creates a strong muscle corset. Therefore, the purpose of the study was to study the impact of swimming on the physical fitness of girls of primary school age. During the study, we used an analysis of scientific and methodological literature on the topic of the study, studying the impact of swimming on the physical fitness of girls aged 7-9. During the study, it was found that swimming classes for 16 weeks contribute to a significant improvement in the dynamic strength endurance of the muscles of the shoulder girdle according to the results of the tests "flexion and extension of the arms in a supine position", "pull-ups on the crossbar in a hanging position", dynamic strength endurance of the abdominal muscles and hip joint extensors in girls aged 7-9. The results of the test “forward tilt of the trunk from a sitting position” improved in all girls after 16 weeks. No significant improvements in the average values of speed, agility, and explosive strength were recorded in girls. In girls who participated in the study, a significant improvement in the result of performing hand dynamometry with the right hand was found.